21.11.7 Chemoselective Ligation Methods Based on the Concept of Native Chemical Ligation - Malins,L. R.; Payne,R. J. (Knowledge Updates 2021/3, 2021)
This chapter extends from the earlier Science of Synthesis contribution on peptide synthesis (Section 21.11) and focuses on recent developments in chemoselective ligation chemistry based on the logic of native chemical ligation. Synthetic strategies that broaden the scope and versatility of the ligation reaction and that have been widely adopted for the preparation of homogeneous peptides and proteins are highlighted. Methods enabling the efficient preparation of peptide ligation precursors are also included in this chapter.
Keywords: Referencework; Science of Synthesis; ligation; cysteine; selenocysteine; desulfurization; deselenization; acyl shift; peptides; proteins; amides; solid-phase peptide synthesis; peptide coupling